Adaptive fractional order terminal sliding mode control of a doubly fed induction generator- based wind energy system (2017)
The dynamic model of a doubly fed induction generator (DFIG)-based wind energy system is subjected to nonlinear dynamics, uncertainties, and external disturbances. In the presence of such nonlinear effects, a high-performance control system is required to guarantee the smooth and maximum power transfer from the wind energy system to the ac grids. This paper proposes a novel fractional order adaptive terminal sliding mode control system for both the rotor and grid side converters of the DFIG system. The stability of the closed loop is ensured using the fractional order Lyapunov theorem. Numerical results are presented to show the superiority of the proposed control method over the classical sliding mode control system and the proportional integral controllers.